Fibronectin regulates the self-renewal of rabbit limbal epithelial stem cells by stimulating the Wnt11/Fzd7/ROCK non-canonical Wnt pathway. (August 2019) - Zheng, Mingyue; Tian, Chenglei; Fan, Tingjun; Xu, Bin
Abstract: Microenvironmental factors regulate stem cell fate. Fibronectin (FN), a key extracellular matrix component of the microenvironment, has been linked to various stem cell behaviors. However, how FN controls self-renewal, proliferation, and homeostasis of limbal stem cells remains unclear. Our study investigated the roles of FN in the self-renewal of rabbit limbal epithelial stem cells (rLESCs) by assessing rLESC proliferation and stemness in the presence and absence of FN. We further examined the effect of FN on non-canonical Wnt signaling during rLESC proliferation by evaluating the expression of cell cycle regulators. We found that rLESC proliferation increased after FN treatment and that 12.5 μg/cm 2 FN maintained rLESC stemness. FN facilitated rLESC self-renewal by promoting Wnt11 and Fzd7 interaction. Furthermore, FN modulated cell cycle regulators to enhance rLESC proliferation via the upregulation of ROCK1 and ROCK2. Our study provides new insights into the mechanism through which FN regulates the self-renewal of rLESCs; specifically, this occurs via stimulation of the Wnt11/Fzd7/ROCK non-canonical Wnt pathway. The roles of FN in the self-renewal of limbal epithelial stem cells should be further investigated for the potential treatment of limbal deficiency. Highlights: FN improves the self-renewal of rabbit limbal epithelial stem cells (rLESCs). rLESC proliferation is enhanced through modulating ROCK1/2 and cell cycle regulators. FN regulates rLESC self-renewal by stimulating the Wnt11/Fzd7/ROCK non-canonical Wnt pathway.